FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI MENGGUNAKAN BENIH PADI SAWAH BERSERTIFIKAT DI DESA TUAH INDRAPURA KECAMATAN BUNGARAYA KABUPATEN SIAK PROVINSI RIAU - Fenny Widya Sari; Rini Nizar; Hamdan Yasid (DINAMIKA PERTANIAN, 2025)
Seed is one of the fundamental inputs in crop production. Certified seeds are those that have undergone a seed certification process supervised and approved by the Seed Certification and Control Agency (Balai Pengawasan dan Sertifikasi Benih/BPSB). Certified rice seeds have long been recommended to farmers, as their use provides numerous benefits, such as increased production and improved farmers' incomes. This study aimed to identify the characteristics of farmers and the profile of lowland rice farming, and to analyze the factors influencing farmers' decisions to use certified lowland rice seeds in Tuah Indrapura Village, Bungaraya Subdistrict, Siak Regency, Riau Province. The research used a survey method, with a total sample of 81 lowland rice farmers selected through purposive sampling. Data were analyzed using descriptive statistics and logistic regression. The results showed that the average age of farmers who used certified seeds was 47.59 years, while those who did not use certified seeds averaged 49.36 years, placing both groups in the productive age category. The average education level was 9.59 years (equivalent to high school) among users of certified seeds and 8.66 years (equivalent to junior high school) among non-users. The average farming experience was 18.49 years for certified seed users and 17.18 years for non-users. The average number of dependents was 2.57 persons for certified seed users and 2.41 persons for non-users. The average landholding was 1.08 hectares for certified seed users and 1.02 hectares for non-users. The factors that significantly influenced farmers' decisions to use certified lowland rice seeds were production, seed price, education, and income. Meanwhile, farming experience and land size did not significantly influence the decision to use certified seeds in Tuah Indrapura Village, Bungaraya Subdistrict, Siak Regency, Riau Province.